EMBRYONIC DEVELOPMENT AND HACTHING OF Meloidogyne enterolobii (NEMATODA: MELOIDOGYNIDEAE) - de Moura, Romero Marinho; Lira, Vanessa Lopes (Anais da Academia Pernambucana de Ciência Agronômica, 2020)
It was studied and documented the embryonic development of the plant parasitic nematode Meloydogyne enterolobii, the guava root-knot nematode. The specimens used were collected from a pure culture of this nematode species maintained under greenhouse conditions. For the analysis of the events, it was used young (whites) and old (browns) egg messes, following standard procedures. The results pointed out that the different stages of the embryonic development of the studied nematode followed the similar pattern described in the literature for others Tylenchomorpha.